mGlu2 mechanism-based interventions to treat alcohol relapse - Vengeliene, Valentina; Spanagel, Rainer (Frontiers in pharmacology, 2022)
Recently we identified a deficiency in metabotropic glutamate receptor 2 (mGlu2) function in the corticoaccumbal pathway, as a common pathological mechanism underlying alcohol-seeking and relapse behavior. Based on this mechanism, we hypothesized that mGlu2/3 agonists and mGlu2 positive allosteric modulators (PAMs) may be effective in reducing relapse-like behavior. Two mGlu2/3 agonists, LY379268 and LY354740 (a structural analog of LY379268 six-fold more potent in activating mGlu2 over mGluR3), were tested in a well-established rat model of relapse, the alcohol deprivation effect (ADE) with repeated deprivation phases. Since these agonists do not readily discriminate between contributions of mGlu2 and mGluR3, we also tested LY487379, a highly specific PAM that potentiates the effect of glutamate on the mGlu2 with less specificity on other mGlu receptor subtypes. Both LY379268 and LY354740 significantly and dose-dependently reduced the expression of the ADE. No significant changes in water intake, body weight and locomotor activity were observed. Importantly, repeated administration of mGlu2/3 agonist did not lead to tolerance development. mGlu2 PAM LY487379 treatment significantly reduced expression of the ADE in both male and female rats. Combination treatment of mGlu2/3 agonist and PAM had similar effect on relapse-like drinking to that seen in mGlu2/3 agonist treatment alone. Together with other preclinical data showing that PAMs can reduce alcohol-seeking behavior we conclude that mGlu2 PAMs should be considered for clinical trials in alcohol-dependent patients.
Gesehen am 10.10.2023